A novelty route for smartphone-based artificial intelligence approach to ophthalmic screening. Issue 10 (11th June 2020) - Jheng, Ying-Chun; Chou, Yu-Bai; Kao, Chung-Lan; Yarmishyn, Aliaksandr A.; Hsu, Chih-Chien; Lin, Tai-Chi; Chen, Po-Yin; Kao, Zih-Kai; Chen, Shih-Jen; Hwang, De-Kuang
Abstract : Artificial intelligence (AI) has been widely applied in the medical field and achieved enormous milestones in helping specialists to make diagnosis and remedy decisions, particularly in the field of eye diseases and ophthalmic screening. With the development of AI-based systems, the enormous hardware and software resources are required for optimal performance. In reality, there are many places on the planet where such resources are highly limited. Hence, the smartphone-based AI systems can be used to provide a remote control route to quickly screen eye diseases such as diabetic-related retinopathy or diabetic macular edema. However, the performance of such mobile-based AI systems is still uncharted territory. In this article, we discuss the issues of computing resource consumption and performance of the mobile device-based AI systems and highlight recent research on the feasibility and future potential of application of the mobile device-based AI systems in telemedicine.